Analisis Faktor Yang Memengaruhi Keputusan Dalam Memilih Tempat Indekos Pada Mahasiswa Universitas Quality - Ompusunggu, Vina Maria (MTU PRESS, 2022)
Decision making is basically a process of selecting from various alternative actions that may be chosen in the hope that it will produce the best decision. The purchase decision is the stage or decision process where consumers actually (actually) make product purchases. Basically, the buying decision-making process that will be carried out by consumers will go through several stages called the five-stage model decision-making process, namely problem recognition, information search, alternative evaluation, purchase decisions, post-purchase behavior. Higher education as an educational unit that organizes higher education plays a very important role in creating quality human resources. Prospective students, especially those who are not residents of the city where the college is located, will face a major problem, namely where they will live while they study at the college. In order to get a boarding house as desired, there are several factors that may be considered by students before deciding which boarding house to choose. Some factors include, students choosing a boarding house by paying attention to the surrounding environment, location, distance, comparison of rental prices as much as 87%, facilities provided by boarding house services as much as 57.7%, or even choosing a boarding house based on references from family, friends. one campus, and the presence of friends from the same area as much as 56.1%. The condition of the living environment is one of the variables that influence students in choosing a boarding house. Students who cannot afford to rent a boarding house are looking for a landlady who can live in their house and help with housework. In addition to getting a free place to live, you can also earn income and life experience.